Desain Gedung Auditorium UBB Menggunakan Konsep Green Building - Gladys Trista Lituhayu; Ananda Ariski Putri; Yuska Ainal Akbar; Desy Yofianti (FTSP Universitas Jayabaya, 2025)
The Auditorium Building of Universitas Bangka Belitung is designed by applying the green building concept as an effort to support sustainable development within the campus environment, which remains natural and surrounded by green areas. This research uses a descriptive-qualitative method with a sustainable architectural design approach that includes site analysis, space requirements, and design modeling using AutoCAD, SketchUp, and D5 Render software. The design results show that the application of green building principles is realized through the building’s efficient orientation toward the direction of the sun and wind, the use of cross ventilation and natural lighting, the utilization of local environmentally friendly materials such as Wood Plastic Composite (WPC) and low-e glass, as well as a rainwater management system for water efficiency. The roof design is inspired by the shape of a crab shell as a representation of Bangka’s local identity and a symbol of environmental resilience. Overall, this design is expected to become a prototype of an environmentally conscious campus building that is energy-efficient, functional, and reflects local wisdom.